Forming students' imagination of space while studying graphic subjects - Kusebaev, Уалихан; Zhumabayev, Атағали (Рroblems of engineering and professional education, 2023)
Ways to improve the quality of training of future specialists are considered in this article. The role of drawing geometry and engineering graphics in the formation and development of students' spatial representations, as well as the ability to operate graphic models of objects, is explained.